2010
DOI: 10.1021/om100346x
|View full text |Cite
|
Sign up to set email alerts
|

Bis(allenylidene) Complexes of Palladium and Platinum

Abstract: trans-Bis(alkynyl)palladium complexes, trans-[(PEt 3) 2 Pd(-CtCC{dO}NR 2) 2 ] (NR 2 = NMe 2 (2a), N(CH 2) 4 (2b)), were synthesized by two different methods: (a) by copper-catalyzed reaction of HCtCC(dO)NR 2 with [PdCl 2 (PEt 3) 2 ] under basic conditions and (b) by treating HCtCC(dO)NR 2 with AgNO 3 followed by transmetalation of the alkynyl ligand from silver to [PdCl 2 (PEt 3) 2 ]. The reaction of AgCtCC(dO)NMe 2 (3a) with trans-[Br(P i Pr 3) 2 PdCtCC(dO)N(CH 2) 4 ] (5) affords a complex containing two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…39 In addition, a triplet of the C^CePd (d¼108.1 ppm) carbon atom is visible in the 13 C NMR spectra of 18 (J PC ¼3.85 Hz) which confirms that the two phosphine ligands are mutually trans. 48,49 This value is in agreement with literature known trans-[bis(3-(pentamethyleneamino)-3-methoxy-1,2-propadienylidene)bis (triethylphoshine)palladium(II)] alkynyl complexes (d¼104.3 ppm 46 ), and is shifted downfield in comparison to their corresponding allenylidene complexes (d¼97.3 ppm 46 ). In the IR spectra one band of the C^C-stretching vibration is detected at 2104 cm À1 , and the anion hexafluorophosphate can be seen by a signal at d¼À144.5 ppm in the 31 P NMR spectrum.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…39 In addition, a triplet of the C^CePd (d¼108.1 ppm) carbon atom is visible in the 13 C NMR spectra of 18 (J PC ¼3.85 Hz) which confirms that the two phosphine ligands are mutually trans. 48,49 This value is in agreement with literature known trans-[bis(3-(pentamethyleneamino)-3-methoxy-1,2-propadienylidene)bis (triethylphoshine)palladium(II)] alkynyl complexes (d¼104.3 ppm 46 ), and is shifted downfield in comparison to their corresponding allenylidene complexes (d¼97.3 ppm 46 ). In the IR spectra one band of the C^C-stretching vibration is detected at 2104 cm À1 , and the anion hexafluorophosphate can be seen by a signal at d¼À144.5 ppm in the 31 P NMR spectrum.…”
Section: Resultssupporting
confidence: 91%
“…It is literature-known that the 13 C NMR detection in related complexes is difficult or impossible. 39,47,49 …”
Section: Resultsmentioning
confidence: 99%
“…To our delight, this complex undergoes a dismutation reaction, affording bis(triphenylphosphine)gold( i ) along with the bis(allenylidene)gold( i ) complex 8 , which was isolated in 11% yield as a moisture and air stable solid ( Scheme 2 ). So far, only bis(allenylidene) complexes of Ag, 6 Pd, 6 , 18 Pt, 18 and Ru 16 have been isolated. 1 H and 13 C NMR spectroscopy of 8 clearly shows a symmetrical structure.…”
Section: Resultsmentioning
confidence: 99%
“…Conductivity measurements gave similar results as those reported above. We therefore assume that analogous equilibria exist in both cases; however, while in our study the 1 : 1 complex 3 was found in the solid state, (4). Symmetry transformation used to generate equivalent atoms (Cl , Ag ): −x + 1, −y + 2, −z + 1. a 2 : 2 ion-pair complex analogous to 2B was obtained in the reported case [26].…”
Section: Resultsmentioning
confidence: 94%
“…In another related study, Fischer and coworkers [4] have prepared Pd(II) complexes 7 with two 3-alkoxy-3-dialkylaminoallenylidene ligands (or zwitterions − C≡C-C + (OR)(NR 2 ), depending on the point of view). Based on certain NMR and IR data, these authors have emphasized the strong contribution of the alkynyl-type resonance form to the bonding in these so-called bis(allenylidene) complexes.…”
Section: Resultsmentioning
confidence: 99%